2021
DOI: 10.1021/acs.est.0c07232
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Di-n-butyl Phthalate Metabolites in Arabidopsis thaliana and Potential Deconjugation in Human Microsomes

Abstract: Plasticizers, due to the widespread use of plastics, occur ubiquitously in the environment. The reuse of waste resources (e.g., treated wastewater, biosolids, animal waste) and other practices (e.g., plastic mulching) introduce phthalates into agroecosystems. As a detoxification mechanism, plants are known to convert phthalates to polar monophthalates after uptake, which are followed by further transformations, including conjugation with endogenous biomolecules. The objective of this study was 2-fold: to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 71 publications
(147 reference statements)
1
33
0
Order By: Relevance
“…Amino acid conjugates such as jasmonoyl isoleucine can have key roles in stress response, plant defense, and plant growth . Plants also form amino acid conjugates with xenobiotics, as evidenced by amino acid conjugation with the anticorrosive benzotriazole, the tire rubber vulcanizer 2-mercaptobenzothiazole, and the plasticizer di- n -butyl phthalate in Arabidopsis . Some of these conjugates are structurally analogous to natural plant compounds such as indoles, which have critical functions in hormone storage. More work is necessary to determine the function of the amino acid-conjugated product discovered in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Amino acid conjugates such as jasmonoyl isoleucine can have key roles in stress response, plant defense, and plant growth . Plants also form amino acid conjugates with xenobiotics, as evidenced by amino acid conjugation with the anticorrosive benzotriazole, the tire rubber vulcanizer 2-mercaptobenzothiazole, and the plasticizer di- n -butyl phthalate in Arabidopsis . Some of these conjugates are structurally analogous to natural plant compounds such as indoles, which have critical functions in hormone storage. More work is necessary to determine the function of the amino acid-conjugated product discovered in this study.…”
Section: Resultsmentioning
confidence: 99%
“…For data from UPLC-ESI-HRMS, the algorithm tracked 52 potential isotopologue pairs, and 13 isotopologue pairs were annotated as potential TPs (Figure , Table S3, and Figures S6–S10), which accounts for highly to 25% of the total extracted features. Two previous studies found seven and six isotopologue pairs as potential TPs of contaminants by MetExtract II or X13CMS, respectively. , By our proposed pipeline, 13 TPs of pyrene were annotated, proving its higher performance with cost-effective properties.…”
Section: Resultsmentioning
confidence: 73%
“…Two previous studies found seven and six isotopologue pairs as potential TPs of contaminants by MetExtract II or X13CMS, respectively. 38,39 By our proposed pipeline, 13 TPs of pyrene were annotated, proving its higher performance with cost-effective properties. Four isotopologue pairs detected from UPLC-ESI-HRMS data (e.g., M 221 , [M + H] + , Table S3) were further tracked by GC-EI-HRMS (e.g., M 220 , [M] + , Table S4).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Phase II reactions, amino acid conjugation, sulfation, glycosylation, and more are always considered as detoxification pathways for plants. Compared with the parent CPs, the conjugation metabolites were less toxic, more soluble for excretion, or easier to be sequestrated or incorporated into the cell walls (Phase III) to reduce damage to plants. ,, However, several works reported that when these conjugation metabolites in plants were taken by humans and other living organisms, they were deconjugated by enzymes, such as glucuronidase and sulfotransferases, to release the active compounds derived to conjugates. In addition, as shown in previous works, toxicity effects of some metabolites, especially the hydroxylation metabolites of pollutants, were higher than their parent compound. , The abiotic and biotic transformations in the exposure system led to diversity of hydroxylation products for CP-4. Hence, the potential effects of the verified transformation products in agricultural plants should be seriously concerning.…”
Section: Resultsmentioning
confidence: 89%